PILEA, an Advanced Hybrid Lightweight Algorithm utilizing Logical Mathematical Functions and Chaotic Systems - Mohammed, Zahraa A.; Hussein, Khalid Ali (Engineering, Technology & Applied Science Research, 2024)
In information security, data encryption plays a crucial role in preventing unauthorized access. Traditional methods often fall short when faced with sophisticated cyber threats. This research presents a hybrid encryption technique that integrates a recently devised 5D chaotic system, effectively bolstering data security by encoding information in an intricate, puzzle-like structure. This approach thwarts easy access to sensitive data, thus safeguarding them from potential interception and exploitation. The proposed encryption method combines the Linear Encryption Algorithm (LEA) and the Advanced Encryption Standard (AES) to create the Parallel Improved LEA (PILEA), blending key components of both algorithms to enhance data security. By integrating AES’s S-box, Shift Rounds, Mix Columns, and Add Round Key operations, the PILEA significantly raises the complexity of the encrypted data, making them more resistant to unauthorized decryption attempts. A key innovation of this system is the use of a chaotic system for key generation, resulting in a strong, nonlinear, and dynamic key stream. Furthermore, by operating the entire system in a parallel mode, the proposed approach aims to decrease the number of rounds in the encryption process and the overall execution time for encryption and decryption. These enhancements further strengthen the encryption system’s resilience against infiltration by malicious entities. Experimental results show that the PILEA method can withstand various types of cryptographic attacks, provides reduced computation times, and produces a highly random keystream, as confirmed by the NIST statistical test suite for randomness.